Healthiness of Portuguese Ready to Eat Breakfast Cereals using three international nutritional profile models - Santos, Mariana (2019)
In Portugal according the most recent Health Behaviour in School-aged Children study (HBSC) 90% of the boys and 91% of the girls aged 11 eat breakfast every weekday. Breakfast Cereals and Children's Cereals are included in the group of foods that contribute to the consumption of 30.7% of simple sugars, representing more than 10% of the energy intake in 15.4% of the national population. The nutritional quality of readyto- eat breakfast cereals (RTECs) is variable and can be considered as highly processed and to have higher contents in sugar, mainly those marketed to children. Nutrient profiling according World Health Organization (WHO) definition “is the science of classifying or ranking foods according to their nutritional composition for reasons related to preventing disease and promoting health”. The objective of this study was to compare the healthiness of RTECs by three existing nutrient profiling models, the EU Pledge system, the WHO-Euro model, and the UK model (Ofcom). We selected nutrient profiling models that were applied for different purposes and target groups to enhance the reliability of the results. A Convenient sample was drawn and data was collecting from three food retail chains in the Lisbon region. A total of 39 samples RTECs were evaluated using three nutrient profiling models. Nutrient content of energy (Kcal), saturated fat (g), sugar (g) and sodium (mg)/salt (g). was analysed per 100g of each product. For total sugar content, 56.4% (n=22) and 15.4% (n=6) of RTECs met the criteria EU Pledge system and WHO-Euro model, respectively. For sodium and salt 97% (n=38) of RTECs met the criteria for EU Pledge system and WHO-Euro model. All the RTECs analysed had higher OFCOM cut-off scores (≥4). Nutrient profiling models seem to be an important tool in supporting public health policies particularly the ones to evaluate and improve nutritional quality of foods.